Pseudo-Nitzschia sp (Bacillariophyceae), seasonal distribution in the lagoon of Nador (Morroco) - Riouchi Ouassila (EDP Sciences, 2021)
The goal of this study is to look into the dominance of diatoms, specifically the genus “Pseudo-Nitzschia Sp” at the Nador lagoon level and how it relates to the physicochemical parameters of the environment. From the four sampling stations and for two seasons (spring and summer 2018). This diatom of the genus “Pseudo-Nitzschia Sp” includes toxic species capable of producing domoic acid (DA), a neurotoxin responsible for amnesic intoxication syndrome in humans. During sampling, the species “PseudoNitzschia Sp” showed variable cell densities between stations and seasons. The dominate microalgae were observed during the spring period with a maximum concentration of (4000 Cells / l). And a low viscosity during the summer seasons (140 Cells / l).